ANALISIS ISI PESAN DAKWAH PADA ALBUM “SALAM” KARYA HARRIS J - Aminah, Nur; Hermawati, Hermawati (Journal of Islamic Studies, 2023)
Music is one of the da'wah media that has been used by many people, one of which is by Harris J. In Harris J's music album, the songs contain messages and meanings that contain da'wah messages for listeners with the aim that listeners can feel and take meaning in the lyrics included in songs by Harris J. One of Harris J's albums which contains songs with da'wah messages is the album